Analysis of authorizations for highly complex medication procedures for kidney transplant patients in the State of Rio de Janeiro (Research, Society and Development, 2021)
Maintenance immunosuppressive therapy is administered to almost all kidney transplant recipients to help prevent acute rejection and kidney graft loss among genetically different individuals. The present study aimed to analyze the dispensing of drugs from the Specialized Component of Pharmaceutical Assistance for the treatment of patients undergoing kidney transplantation in the State of Rio de Janeiro in the period from 2008 to 2013. For this purpose, a descriptive study was conducted that included 156,527 records of APAC for selected drugs for kidney transplants. The results showed that 55.7% of the APAC generated were for male patients, 28.1% for patients aged 40 to 49 years. 78.4% of the APAC produced were for patients who lived in municipalities in the metropolitan region of the State of Rio de Janeiro. The main secondary diagnosis was chronic kidney disease (30.9%). The chemical group that most generated APAC was antiproliferative, with mycophenolate mofetil in greater quantity. Among the other chemical groups, calcineurin inhibitors and rapamycin inhibitors, the drugs that generated the most APAC were tacrolimus and sirolimus, respectively. There are few studies on the use of drugs on the maintenance of kidney transplantation in Brazil. The results observed indicate that the drugs that were dispensed the most are not the drugs of first choice for the maintenance treatment of kidney transplantation. This result allowed us to have a profile of the medications that have the greatest impact on the treatment of patients undergoing maintenance therapy for kidney transplantation, which can help for future planning of pharmaceutical assistance in SUS.